Financial Planning in Micro and Small Commercial Enterprises in Chachapoyas (2018-2023) - Salazar, Carlos Alberto Hinojosa; Acosta , Robert Wagner Ocadio; Serván , Segundo Ramón Salazar; Melendez , Milagros Natividad Hinojosa; Tuesta , Jesus Ermilia Reyna; Puerta , Carlos Andrés Rojas (Journal of Ecohumanism, 2024)
This study examines the influence of financial planning on the economic sustainability of commercial micro and small enterprises (MSEs) in Chachapoyas, Peru, during the period 2018-2023. Using a descriptive cross-sectional design and a sample of 100 MSEs, three key dimensions were assessed: financial resource management, investment planning, and risk management. The results show that most companies achieve a medium or high level of financial planning, although only a minority implement advanced practices. The research highlights the importance of strengthening budgetary control, investment strategies and risk management to improve the resilience and adaptability of these companies. This analysis provides a theoretical and practical perspective on financial planning in MSEs, with recommendations to foster their sustainable development and stability in a changing economic environment.